Food Security: The Role of Social Capital in Indonesia Rural Area - Estiana Rusmawati; Djoni Hartono (Economics Development Analysis Journal, 2021)
Data from Food Security Agency or BKP in Indonesian indicate that rural areas food security islower than urban areas. Regarding this fact and findings of previous studies, the present study attempted to determine the effect of social capital (bonding and bridging) on rural households’ foodsecurity. Compared to the previous study which involved few areas, the present study investigated more representative areas at national level. It covered 38,968 rural households in 34 provinces allover Indonesia taken from Susenas BPS 2018. To analyze the data, the researchers employed Ordinary Least Square (OLS) to examine the association of continuous dependent variable with several independent variables. The results showed that both bonding and bridging as social capital gained positive and significant correlation with food security. Further, it also explained bridging contributed stronger effects on food security than bonding. Thus, these results recommend improvement in the food security policy in Indonesia and provide directions for the future studies.